Belief and legal philosophy: a conceptual framework for Christian scholarship in undergraduate legal education - S. de Freitas (Koers : Bulletin for Christian Scholarship, 2009)
Legal education in South Africa has arrived at a discursive juncture that demands clarity on what the “purpose” of legal education should be. Debate on the purpose of legal education, more specifically for the Christian law student, becomes especially important in a society dominated by positivism, mate-rialism and pragmatism. With specific reference to the under-graduate Christian law student, this article firstly explains that the purpose of legal education should include the nurturing of the student’s belief – a belief encompassing his/her foun-dational perspective(s) on reality. Secondly, in order to achieve the proper nurturing and development of the Christian law student’s belief, the importance of the teaching of legal philo-sophy is explained. In this regard, proposals are postulated pertaining to specific means by which such nurturing and development of the undergraduate Christian law student’s foundational belief can be attained.